Analisis Penjualan dan Faktor-Faktor yang Mempengaruhinya pada Usaha Industri Kecil Meuabel Kayu di Kota Banjarmasin - Sulaiman, Sulaiman (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2017)
This research is amed to do serve the sales development of wood furniture and to test the factors that influence it. Variables that are taste in thie research are variable X1 = price level, X2 = product amount, X3 = product varity, X4 = supply amount, and X5 = sales promotion. The sales development, if seen through index, show that in the year 2012, 15 (75%0 of the samples gained the increase, hwile the rest suffered from sales decrease; then in the year 2013, 14 (70%) of the samples gained sales increase, the rest 6 company suffered from sales decrease. If observed through the calculation the aggregate inkdex reached over 100% in the year 2012 and 2013; this means that the sales of the whole company, used as research samples, increase than the previous year. The result of variable test that used the F test show that F ratio = 13.401, bigger than the table F = 2,71; this means that the price level, product amount, product amount, supply amount, and sales promotion simultaneously give significant effects to the sales amount variable, as can be seen through the p value, that p (?) value = 1.680E-08 is lower than p value = 0,05.Key words : sales amount, price level, product amount, production varity, supply amount, sales promotion